Antibacterial Potential of Methanolic Extracts from Azadirachta indica (Neem) Leaves against Gram-Positive and Gram-Negative Bacteria - Kumari, Neema; Jaiswal, Niketa; Sharma, Mamta; Poonam; Asthana, Pranjul; Dixit, Priyanka; Mishra, Abhishek (Contemporary Research and Perspectives in Biological Science Vol. 4, 2024)
With the increasing rate of antibiotic/multidrug resistance and the growing demand for plant-based therapies, Azadirachta indica (neem) emerges as one of the leading medicinal plants due to its wide range of compounds with antioxidant and cytotoxic activities. This study analysed the A. indica leaf methanol extract for its antibacterial activity against Gram-positive (Staphylococcus aureus) and Gram-negative (Pseudomonas aeruginosa and Escherichia coli) bacteria using the agar diffusion assay with methanol extracts of varying concentrations (5%, 10%, 20%, and 40%) initially for S. aureus and P. aeruginosa. Later, methanol extracts with concentrations of 0.5%, 1.0%, 1.5%, and 2.0% were used for S. aureus and E. coli. Gentamicin was used as a positive control. The results indicated the antibacterial activity of the A. indica leaf methanol extract against all three bacteria, irrespective of the concentration used. However, compared to gentamicin, the antibacterial activity of A. indica was relatively lower. These findings indicate the potential of A. indica as a plant-based antibacterial agent, offering an alternative or complementary treatment strategy to combat antibiotic/multidrug resistance. Further clinical studies/trials on the leaf extract are required to ensure its safety for human use.